Corrosion of hot-dip galvanized steel reinforcement - Figueira,R. B. (2014)
In the past several years hot-dip galvanized steel (HDGS) has successfully been used to extend the service life of reinforced concrete structures, mainly due to its low cost and high corrosion resistance compared to mild steel. However, the initial corrosion behaviour of the galvanized coating when embedded in concrete and how that behaviour may be affected by the surface composition of the coating remains unclear. When HDGS is embedded in fresh concrete (a highly alkaline environment), the zinc coating corrodes vigorously until passivation occurs and the concrete hardens. This leads to two main concerns, namely, the high initial corrosion rate, which may remove so much zinc that this leads to insufficient galvanic protection of the underlying steel, and the hydrogen production (in the corresponding cathodic half-cell reaction) which may increase the porosity of the adjacent cement paste and reduce the bond strength between the bar and the concrete. To avoid, or at least minimize, this initial reaction the use of chromates has been implemented. However, due to the toxicity of hexavalent chromium, environmental and human health concerns have restrained their use and alternatives are being studied all over the world. In this paper, the coatings and pre-treatments studied at an academic level in the last few years (2001-2014) have been reviewed together with the corrosion mechanisms of HDGS in contact with high alkaline environments and the role of Cr(VI) in inhibiting the initial zinc corrosion process.